MicroCT Advanced Imaging of the Foot and Ankle: Technique Guide - Jonathan Day MD (Foot & Ankle Orthopaedics)
Background: Recent advances in micro-computed tomography (MicroCT) imaging have enabled detailed investigations of human microvascular anatomy, providing new insights that may influence treatment options and optimize local reparative potential. This article describes a reproducible cadaveric perfusion technique for visualizing foot and ankle microvasculature using MicroCT, designed to support anatomical research and surgical planning studies. Methods: Ten matched pairs of fresh-frozen cadaveric lower limbs were used to develop this protocol. An 18-gauge angiocatheter was used to cannulate the anterior and posterior tibial arteries for perfusion of the foot and ankle, or the popliteal artery for perfusion of the entire lower leg. Clearing was performed sequentially with 0.9% saline, 3% hydrogen peroxide, and water. Perfusion was performed with a 50% barium sulfate/2.5% gelatin solution. Confirmatory images were obtained using mini c-arm fluoroscopy. Final images were obtained for microvascular assessment using a commercial MicroCT scanner. Integrity of the perfusate was visually evaluated on MicroCT over the course of 4 freeze-thaw cycles spanning 2 months. Results: All intraosseous and extraosseous microvascular structures were successfully visualized using MicroCT of the cadaveric lower extremities. Microvasculature was perfused in continuity without incidence of contrast extravasation. When present, intraosseous nutrient arteries of the first and fifth metatarsal, and branches of the tarsal sinus artery were appreciated. Contrast material remained visually consistent even after preforming surgical resections and undergoing multiple freeze-thaw cycles. Conclusion: This standardized perfusion technique was effective in the visualization of microvasculature in the foot and ankle. In addition to 3-dimensional mapping using MicroCT, this reproducible protocol can be used in numerous advanced imaging applications, including microvascular assessment following surgical reconstructions and instrumentation. Clinical Relevance: A refined understanding of the microvascular anatomy of the foot and ankle using MicroCT perfusion imaging can potentially guide surgical techniques to minimize iatrogenic injury and optimize healing.